Tris-bipyridine based dinuclear ruthenium(ii)–osmium(iii) complex dyads grafted onto TiO2 nanoparticles for mimicking the artificial photosynthetic Z-scheme. Issue 6 (30th January 2017) - Favereau, Ludovic; Makhal, Abhinandan; Provost, David; Pellegrin, Yann; Blart, Errol; Göransson, Erik; Hammarström, Leif; Odobel, Fabrice
Abstract : A Ru(ii )–Os(iii ) dyad was grafted on TiO2 to achieve Z-scheme charge separation, but photoinduced electron transfer was shown to be a minor reaction pathway in this system. Abstract : The Z-Scheme function within molecular systems has been rarely reported for solar energy conversion although it offers the possibility to achieve higher efficiency than single photon absorber photosystems due to the use of a wider range of visible light. In this study, we synthesized and investigated the electrochemical and spectroscopic properties of two new dyads based on ruthenium and osmium tris-bipyridine complexes covalently linked via a butane bridge to explore their ability to realize the Z-scheme function once immobilized on TiO2 . These dyads can be grafted onto a nanocrystalline TiO2 film via the osmium complex bearing two dicarboxylic acid bipyridine ligands, while the ruthenium complex contains either two unsubstituted bipyridine ancillary ligands (RuH–Os ) or two (4, 4′-bis-trifluoromethyl-bipyridine) ancillary ligands (RuCF3 –Os ). Transient absorption spectroscopy studies of the Ru(ii )–Os(iii ) dyads with femtosecond and nanosecond lasers were conducted both in solution and on TiO2 . For both conditions, the photophysical studies revealed that the MLCT excited state of the ruthenium complex is strongly quenched and predominantly decays by energy transfer to the LMCT of the adjacent Os(iii ) complex, in spite of the high driving force for electron transfer. This unexpected result, which is in sharp contrast to previously reported Ru(ii )–Os(iii ) dyads, precluded us to achieve the expected Z-scheme function. However, the above results may be a guide for designing new artificial molecular systems reproducing the complex function of a Z-scheme with molecular systems grafted onto a TiO2 mesoporous film.